(untitled) (Research, Society and Development, 2020)
This article aims to problematize and reflect on some elements that hinder the teaching profession in the current conjuncture, in a context of public education, and especially in relation to the way they understand and experience respectful relationships at school. The aceptions presented in this article are based on Historical-Cultural Psychology as a theoretical basis, especially the ideas of Vigotski. It is a qualitative research, with characteristics of action research, being carried out in a state school, located in the interior of the state of São Paulo. To this end, weekly meetings were held with students and teachers in order to promote interventions that sought to result in reflections on respect for school practices. The meetings were held in partnership with two teachers, who are participating in this study. In the analysis, the issue of respect or its absence was highlighted as the main demand on the part of teachers in their relationship with students. It was found that despite the teachers attributing to students the cause of disrespect that they live with on a daily basis, it was observed that such feeling is the result of a more complex context that involves the working conditions that teachers are subjected to, often a source of physical illness and psychological.